Solution route synthesis of PtCuNi nano-particles supported on treated carbon, electrocatalysts for ORR - S. Thungprasert (2018)
© 2014, Hanyang University. All rights reserved. Pt-based ternary compounds supported on carbon have been proposed as a catalyst for oxygen reduction reaction (ORR), with relatively low over-potential, leading to high reaction rates compared to Pt/C catalysts. In this research, samples of 20% wt platinum-copper-nickel (at 2 : 1 : 1 and 6 : 1 : 1 ratios) supported on treated carbon (N115 and Vulcan XC-72) were prepared by solution route method, using NaBH4as a reducing agent. The XRD patterns of the product samples match well with the simulated PtCuNi alloy cubic structure and carbon phases. The SEM and TEM images show well-dispersed metal particles on the treated carbon supports. Metal particle sizes, measured from TEM micrographs, were 2.50-3.00 nm. The electrochemical performance of the PtCuNi alloy at the ratio of 6 : 1 : 1 on carbon Vulcan XC-72 delivered the highest current of 278.70 A/cm2• gptat 600 mV.